Cytokine-Effects on Glucocorticoid Receptor Function: Relevance to Glucocorticoid Resistance and the Pathophysiology and Treatment of Major Depression - Pace, Thaddeus W.W. (2006)
Glucocorticoids play an essential role in the response to environmental stressors, serving initially to mobilize bodily responses to challenge and ultimately serving to restrain neuroendocrine and immune reactions. A number of diseases including autoimmune, infectious and inflammatory disorders as well as certain neuropsychiatric disorders such as major depression have been associated with decreased responsiveness to glucocorticoids (glucocorticoid resistance), which is believed to be related in part to impaired functioning of the glucocorticoid receptor (GR). Glucocorticoid resistance, in turn, may contribute to excessive inflammation as well as hyperactivity of corticotropin releasing hormone and sympathetic nervous system pathways, which are known to contribute to a variety of diseases as well as behavioral alterations. Recent data indicate that glucocorticoid resistance may be a result of impaired GR function secondary to chronic exposure to inflammatory cytokines as may occur during chronic medical illness or chronic stress. Indeed, inflammatory cytokines and their signaling pathways including mitogen-activated protein kinases, nuclear factor-kB, signal transducers and activators of transcription, and cyclooxygenase have been found to inhibit GR function. Mechanisms include disruption of GR translocation and/or GR-DNA binding through protein-protein interactions of inflammatory mediators with the GR itself or relevant steroid receptor cofactors as well as alterations in GR phosphorylation status. Interestingly, cAMP signal transduction pathways can enhance GR function and inhibit cytokine signaling. Certain antidepressants have similar effects. Thus, further understanding the effects of cytokines on GR signaling and the mechanisms involved may reveal novel therapeutic targets for reversal of glucocorticoid resistance and restoration of glucocorticoid-mediated inhibition of relevant bodily/immune responses during stress and immune challenge.